Integration of targeted herbicide application technologies into an integrated weed management program for tomato plasticulture production - Ana Claudia Buzanini; Renato Herrig Furlanetto; Arnold Walter Schumann; Nathan Shawn Boyd (Smart Agricultural Technology)
In plasticulture production systems, weeds emerge in the space between beds (row middles), in transplant holes, and in the case of nutsedge species, through the plastic mulch. In all three locations, herbicides are typically applied with banded or broadcast methods. However, weeds emerge in non-uniform patches, and herbicide applications only where weeds occur would reduce herbicide inputs and costs. Three different targeted spray systems were integrated into an overall in-crop integrated weed management (IWM) program for tomato and compared to conventional application technology. The three comparisons were; 1) banded preemergence herbicides under the plastic mulch versus targeted preemergence herbicides just to the transplant hole, 2) banded versus targeted post-emergence applications in the row middle, and 3) banded versus targeted post-emergence applications on the bed top for nutsedge control. Targeted applications were as effective as the banded application in the row middles and on the bed top. Average actuator accuracy across all applications was 0.8. Total herbicide volume and cost was reduced by 71 and 75 %, respectively, with targeted technologies compared to conventional approaches. This is the first known published research that demonstrates the feasibility and benefits of integrating multiple targeted herbicide application technologies into a single IWM program for vegetables.